High power laser diode arrays - Tang, Xiaohong (2008)
High power laser sources are critical for many applications ranging from optical communication, monitoring and sensing to material modification and studies. In this research project, high power semiconductor diode laser arrays lasing at 808nm wavelength range have been developed. This includes: designed and optimized the semiconductor diode laser and laser array structures; developed MOCVD growth of the semiconductor laser structures with AlGaAsIGaAs material system and InGaAsP/GaAs aluminum free material system; developed the post-growth wafer fabrication processes and packaging of the high power diode laser array bars. High performance semiconductor high power diode laser arrays have been fabricated and tested. The maximum output power of the laser array developed reached >25 W in CW operation, the threshold current is about 7 A and the slop efficiency is better than l W/A. Most performance parameters of the array meet or are superior to the device?s specifications of the project proposal.